Faktor Risiko Postpartum Hemorrhage pada Ibu di Puskesmas Nagrak Kabupaten Sukabumi - Afrijal Muhammad; Titik Respati; Ariko Rahmat Putra (UNISBA Press, 2022)
Abstract. Postpartum hemorrhage is one of the leading causes of maternal death in developing countries, , including Indonesia. The government has made various efforts to prevent maternal deaths, one of which is by reducing the incidence of postpartum hemorrhage. This study aims to determine the factors that influence the cause of postpartum hemorrhage in mothers at the Nagrak Health Center, Sukabumi Regency period 2016 and 2021. This study was conducted using a cross-sectional approach to determine the percentage of risk factors for postpartum hemorrhage. It also describes the relationship of risk factors such as age, parity, education, macrosomia, retained placenta, and history of antepartum hemorrhage in mothers at the Nagrak Health Center Sukabumi Regency. Data analysis in this study was carried out utilizing univariate and bivariate analysis. First, univariate analysis was performed using the frequency distribution for each variable. Then, bivariate analysis was performed to determine the relationship of each risk factor for postpartum hemorrhage to postpartum hemorrhage using the chi-square test. The data of this study were obtained from secondary data, namely by looking at and identifying medical records in the reproductive section of the Nagrak Health Center, Sukabumi Regency, with a total sample of 126 people. The bivariate analysis results showed a relationship if the p-value <0.05. In addition, the results showed that there was a relationship between age and postpartum hemorrhage (p=0.002), parity with postpartum hemorrhage (p=0.018), education with postpartum hemorrhage (p=0.000), macrosomia with postpartum hemorrhage (p=0.02), and retention, Placenta with postpartum hemorrhage (p=0.000). There was no relationship between antepartum hemorrhage and postpartum hemorrhage (p=0.519). Abstrak. Postpartum hemorrhage menjadi salah satu penyebab utama kematian ibu di negara berkembang termasuk di Indonesia. Pemerintah telah melakukan berbagai upaya untuk mencegah kematian ibu salah satunya dengan menurunkan kejadian postpartum hemorrhage. Penelitian ini bertujuan untuk mengetahui faktor – faktor yang mempengaruhi penyebab terjadinya postpartum hemorrhage pada ibu di Puskesmas Nagrak Kabupaten Sukabumi Periode 2016 dan 2021. Menurut WHO, postpartum hemorraghe adalah penyebab utama kematian ibu didunia dan di Sukabumi postpartum hemorraghe merupakan penyebab ketiga kasus kematian ibu. Penelitian ini dilakukan dengan menggunakan metode analitik kuantitatif dengan pendekatan cross sectional untuk mengetahui persentase faktor risiko postpartum hemorrhage dan hubungan faktor risiko seperti usia, paritas, pendidikan, makrosomia, dan riwayat antepartum hemorrhage pada ibu di Puskesmas Nagrak Kabupaten Sukabumi. Data penelitian ini diperoleh dari data sekunder yaitu dengan cara melihat dan mengidentifikasi rekam medis di bagian ponek Puskesmas Nagrak Kabupaten Sukabumi dengan total sampel 126 orang. Hasil analisis bivariat menunjukan terdapat hubungan bila nilai p<0,05. Hasil penelitian bahwa terdapat hubungan antara usia dengan postpartum hemorrhage (p=0,002), paritas dengan postpartum hemorrhgae (p=0,018), pendidikan dengan postpartum hemorrhage (p=0,000) dan makrosomia dengan postpartum hemorrhage (p=0,02). Simpulan Tidak terdapat hubungan antara riwayat antepartum hemorrhage dengan postpartum hemorrhage (p=0,519).